Tissue Culture Technique (Kappaphycus Alvarezii) Using a Somatic Embryogenesis Approach seen from Management and Implementation - Hardianto, Toto; Mustafa; Suleman, Yakub; Nurul Awaliah; Feby Triadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Seaweed is a superior commodity for aquaculture and has the largest production among other superior commodities. The factor that influences the success of seaweed cultivation is the selection of seeds, using good quality seeds because it can increase seaweed production. Therefore, seaweed produced through tissue culture techniques has the advantages and disadvantages of being able to be cultivated in turbid waters, being able to survive at low salinity and being resistant to high rainfall. Meanwhile, to make it more focused, an administrative concept is needed in it regarding management and implementation, so you will see in this journal a very clear administrative approach. The results of the research showed that the stages of the seaweed tissue culture technique started from broodstock acclimatization, sterilization test of the esplank thallus, callus induction, regeneration of embryogenic callus into micropropagules, regeneration of micropropagules into propagules (Plantlets), and maintenance of plantlets. The problem that usually occurs in seaweed tissue culture is human error. This can create sterility during the culture process, so that microorganisms can enter and contaminate the explants. In addition, the entry of microorganisms can be caused by the hole where the hose enters being too wide so that air from outside which may contain microorganisms can enter. The holes created can also cause evaporation or evaporation of sea water so that the salinity rate increases. Another situation that occurs is a lack of air supply from aeration because the internal capacity of the blower which supplies air is weak and uneven. This can cause the explants to accumulate and stick to the walls of the bottle so that nutrient absorption is hampered